Characteristics of paediatric foot arches according to body mass among primary school students in Wrocław, Poland - Sara Górna; Katarzyna Pazdro-Zastawny; Alicja Basiak-Rasała; Mateusz Kolator; Joanna Krajewska; Tomasz Zatoński (BMC, 2022)
Abstract Background The purpose of this study, conducted within the framework of the project entitled 'Let's get the kids moving', was to determine the associations between children's longitudinal and transverse foot arch and their weight, gender and age. Method The pro-health initiative 'Let's get the kids moving' was created by researchers of the Medical University and the Run for Health Foundation. A total of 655 children (51.5% boys) aged 7 to 10 years from primary schools in south-western Poland participated in the study. The mean age of the subjects was 8.7 ± 0.8 years. In all the children, we assessed anthropometric measurements (weight and height) and the longitudinal and transverse arch of the foot under the load of their weight. A two-dimensional foot scanner (Sensor Medica, Italy) was used to examine the plantar part of the children's feet. Results The data collected from the 655 subjects revealed that excessive weight predisposed them to less longitudinal and transverse arching. The foot shape was not differentiated by gender or age. Conclusions Screening school-aged children's footprints can detect abnormalities in the shape of children's feet early on, which allows for early diagnosis of functional or structural flatfoot in children.